Paleosoils and limnic levels in the late Pleistocene and Holocene alluvial successions of the Andean Piedmont of Mendoza (33°-34° LS), Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The late Pleistocene and Holocene alluvial deposits of the Arroyo La Estacada basin, located in the Andean piedmont of Mendoza province between 33° and 34° SL (Fig. 1a-b), are arranged in three conspicuous geomorphological units, a regional aggradational plain (RAP, late Pleistocene - early Holocene), a fill terrace (FT, middle and late Holocene) and a present floodplain (developed ca. 400 yr BP) (A-A’, B-B’, Fig. 1c). The RAP (Figs. 2a, 3a)and the FT (Figs. 2b, 3b) record aggradational and pedologicalproccesses; the latter are more frequents in the Holocene deposits together with abundant sedimentary levels showing high organic matter content (limnic levels).High organic matter content deposits have been studied by the international scientific community, particularly in North America, where some authors discussed the paleoenvironmental and paleoclimaticimplicances of the ‘black mats’ (Haynes, 1968; 2008; Firestone et al., 2007, among others). Toledo (2008) reinforced the idea of a global climatic change by correlating the ‘black mat’ deposits developed in the widely described fluvial sequences of the Central Pampean region of Argentina with those studied in North America. In such a context, this work evalua- tes the paleosoil-limnic level record of the Arroyo La Estacada basin, in the eastern Andean piedmont, with the aim of infering their implicantions in the paleoenvironmental and paleoclimatic dynamics of the central-west Argentinean region during the late Pleistocene and the Holocene. Besides, it provides information to the paleoclimatic framework of southern South America.Alluvial deposits exhibiting paleosoils and limnic levels were sampled using color as a field indicator (Wills et al., 2007, and references therein), in four lithostratigraphic sections located in the banks of Arroyo La Estacada and its tributary the Arroyo Anchayuyo. Qualitative (grain size, color, consistency, type and grade of pedal structure,limit forms and types, cements, redoximorphic features, etc.) and quantitative (organic matter and calcium carbonate contents, table1) attributes were described; also micromorphological analyses were conducted on undisturbed samples (Fig. 4). Results are presented according to a chronological criterion, from the oldest to the youngest paleosoils and limnic levels, based on a chronological calibration of pedosedimentary sequences already reported (Zárate, 2002; Zárate and Páez, 2002; Toms et al., 2004; Zárate and Mehl, 2008) and two new radiocarbon ages (Table 1).The analyzed late Pleistocene and Holocene alluvial deposits record the development of four main pedological processes, affecting not only paleosoils but also limnic levels. They are, organic matter decomposition, calcium carbonate accumulation, redoximorphic features formation and bioturbation.Paleosoils are conspicuous and widely extended along the arroyos basin. They can be recognized in the alluvial deposits as dark bands showing lighter colors downward. Paleosoil top limits are dominantly clear and smooth, the bases are mostly diffuse to smooth and wavy to irregular (Fig. 3a,b). RAP paleosoils are poorly developed showing dearth of pedological features and exiguous horizonation. Calcium carbonate appears in the soil mass and also forming nodules and concretions. FT paleosoils exhibit a greater relative development when comparing with the RAP paleosoils and calcium carbonate is in general absent.Limnic levels are also dark levels, but they present a homogeneous appearance without gradual color variation downwards (Figs. 4a, 5a, h). Its lateral extension is restricted when compared with the one exhibited by paleosoils. Nonetheless some of them can be recognized by several metres throughout the outcrops. The morphology of limnic levels is characterized by the occurrence of lenses formed by organic matter immersed in a fine-grained clastic matrix (Fig. 5h). Its configuration is similar to that described for gyttias o sedimentary peats (Uggla et al., 1969 in Fox, 1985). Limnic levels form due to the precipitation of organic matter suspended in water or by direct action of aquatic organisms (Fox,1985). The Holocene limnic levels are fair indicators of a vegetation productivity increment in the floodplain, especially in waterlogged environments (Fig. 6a,b). Also, they likely record an increase in the amount of organic matter carried by water along the fluvial valley. The major concentration of carbonates in the RAP paleosoils would likely indicate more evaporation in the alluvial basin at the RAP formation time. In turn, the abundance of redoximorphic features in the FT would record waterlogged episodes occurring during the middle and late Holocene, probably in response to frequent water table fluctuations.Analyzed alluvial sequences of the late Pleisto- cene and Holocene record paleoenvironmental and paleoclimatic changes in the eastern Andean piedmont between 33° and 34° SL, in relation to late Pleistocene - Holocene climatic transition. Paleo- soils and limnic levels have resulted in useful tools to calibrate the alluvial sequences and to analyse them geochronologically.
Keywords: Alluvial Successions, Paleosoils, Limnic Levels, Late Pleistocene, Holocene, Eastern Andean Piedmont.